Informed Consent and Debriefing When Deceiving Participants: A Systematic Review of Research Ethics Guidelines. (July 2023) - Verbeke, Kamiel; Krawczyk, Tomasz; Baeyens, Dieter; Piasecki, Jan; Borry, Pascal
Informed consent and debriefing of research participants in studies that use deception are ethical safeguards for which existing scholarly work on their implementation remains variable and insufficiently clear. A systematic review of research ethics guidelines was conducted to sketch a picture of whether, why and how informed consent and debriefing are recommended when using deception. Documents roughly agreed on several general principles, but varied significantly in the specifics of why and whether these safeguards are necessary, in which conditions and how they should be implemented. Various aspects that appear in the literature could not be found in the guidelines. In our review, guidance was integrated and showed a variation of implementation strategies that could help in contextualizing these safeguards.